2023
DOI: 10.1038/s41398-023-02393-7
|View full text |Cite
|
Sign up to set email alerts
|

Mouse mutants in schizophrenia risk genes GRIN2A and AKAP11 show EEG abnormalities in common with schizophrenia patients

Abstract: Schizophrenia is a heterogeneous psychiatric disorder with a strong genetic basis, whose etiology and pathophysiology remain poorly understood. Exome sequencing studies have uncovered rare, loss-of-function variants that greatly increase risk of schizophrenia [1], including loss-of-function mutations in GRIN2A (aka GluN2A or NR2A, encoding the NMDA receptor subunit 2A) and AKAP11 (A-Kinase Anchoring Protein 11). AKAP11 and GRIN2A mutations are also associated with bipolar disorder [2], and epilepsy and develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…Against this backdrop, the phenotype of Grin2a +/− heterozygotes has also been examined recently, and is arguably of more relevance to schizophrenia than are the Grin2a +/− knockouts, given the protein-truncating hemizygous GRIN2A mutations and thence the presumed haploinsufficiency. Herzog and colleagues [ 54 ] used EEG to show that Grin2a +/− mice exhibit attenuated auditory steady-state responses at gamma frequencies, and increased gamma power during sleep, both features that have been observed in schizophrenia. Locomotor activity was also increased.…”
Section: Grin2a Mouse Modelsmentioning
confidence: 99%
“…Against this backdrop, the phenotype of Grin2a +/− heterozygotes has also been examined recently, and is arguably of more relevance to schizophrenia than are the Grin2a +/− knockouts, given the protein-truncating hemizygous GRIN2A mutations and thence the presumed haploinsufficiency. Herzog and colleagues [ 54 ] used EEG to show that Grin2a +/− mice exhibit attenuated auditory steady-state responses at gamma frequencies, and increased gamma power during sleep, both features that have been observed in schizophrenia. Locomotor activity was also increased.…”
Section: Grin2a Mouse Modelsmentioning
confidence: 99%
“…Genetic studies identified AKAP11 LoF as a candidate predisposing gene for both diseases. A study looking at AKAP11 mutant mice found that their EEG patterns resembled those observed in individuals with SCZ 31 . In another study, proteomic profiling of synapses found shared molecular pathway modifications between patients with SCZ, BD, and AKAP11 -mutant mouse models--mainly pathways related to ribosomes, mitochondrial respiration, and vesicle trafficking pathways 34 .…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, mice with Grin2a genetic mutations have been used as a model for schizophrenia based on this hypothesis long before the current genetic evidence. While in humans, the variations of the Grin2a gene were found in the form of point mutations in heterozygous patients, most of the behavioral phenotypes for loss of function in Grin2a were found in NR2A full knockout mice 45,46 . The robust cognitive phenotype in heterozygous Grin2a Y700X+/mice provides an opportunity to dissect neurobiological mechanisms in a system more closely modeling the genetic risks of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%